The Influence Of Education, Training, Talent Management, Andorganizational Culture On Employee Competency At Theregional Secretariat Of Empat Lawang District - Negara, Syahruddin Umar Pranata Negara; Yansyah, Lin; Darmin, Darmin (Universitas Dehasen Bengkulu, 2024)
This research aims to determine and analyze the influence of Education, Training, Talent Management and Organizational Culture together on employee competency at the Empat Lawang Regency Regional Secretariat, either partially or simultaneously. This research uses quantitative research methods with respondents namely the Empat Lawang Regency Regional Secretariat employees, totaling 75 respondents. Testing in this study used multiple linear regression analysis with SPSS (Special Package and Service Solution) version 26 program tools. The research results showed that Education, Training, Talent Management and Organizational Culture were proven to have a significant influence on employee competency at the Empat Lawang Regency Regional Secretariat either partially or simultaneously.